Experimental investigation on physicochemical properties of Iso-Butanol additive in methanol-gasoline blends / Hazim Sharudin ...[et al.] - Sharudin, Hazim; Abdullah, Nik Rosli; Mamat, A.M.I.; Zaharin, M.S.M; A.R., Asiah (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Alcohol fuels such as methanol are popular as an alternative fuel for internal combustion engine because of its economic and environmental advantages over fossil fuel. Blended methanol-gasoline fuels can be improved further by adding higher carbon number such as iso-butanol as they have higher energy content and are able to displace more gasoline fuel. However, the research on the addition of lower ratio iso-butanol in methanol-gasoline fuel properties is not investigated thoroughly. Therefore, this study will focus on investigating the physical and chemical properties of iso-butanol additive in methanol-gasoline blends. Different methanol-gasoline fuel blends were obtained with the addition of 5 vol%, 10 vol%, and 15 vol% iso-butanol into a lower ratio of 5 vol% methanol-gasoline blended fuel. The blended fuel properties determined are density, kinematic viscosity, lower heating value, latent heat of vaporization and Reid of vapour pressure. Characterization of the blends with iso-butanol additive was tested according to specific test standards. From the test results, improvement was recorded at density, kinematic viscosity, and latent heat of vaporization for iso-butanol additive of 5%, 10%, and 15% with 5% of the methanol-gasoline fuel blends. On the other hand, a reduction was recorded for both lower heating value and Reid vapour pressure for all blended fuels with iso-butanol additive in comparison to that of base fuel. No phase separation occurred and the blends were successfully blended in lower ratio volume at specific temperatures. Overall, a lower ratio of the iso-butanol additive on methanol-gasoline blends was found to improve the current existing methanol-gasoline blends.